2021
DOI: 10.1093/nar/gkab1075
|View full text |Cite
|
Sign up to set email alerts
|

m5C-Atlas: a comprehensive database for decoding and annotating the 5-methylcytosine (m5C) epitranscriptome

Abstract: 5-Methylcytosine (m5C) is one of the most prevalent covalent modifications on RNA. It is known to regulate a broad variety of RNA functions, including nuclear export, RNA stability and translation. Here, we present m5C-Atlas, a database for comprehensive collection and annotation of RNA 5-methylcytosine. The database contains 166 540 m5C sites in 13 species identified from 5 base-resolution epitranscriptome profiling technologies. Moreover, condition-specific methylation levels are quantified from 351 RNA bisu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 50 publications
1
33
1
Order By: Relevance
“…Research groups focusing on non-coding RNAs have identified the m 5 C modification of mitochondrial tRNAs and one rRNA ( 11 , 28–30 ), indicating the presence of NSUN2 ( 29 , 31 ), NSUN3 ( 32 , 33 ) and NSUN4 ( 30 , 34–36 ) activity within the mitochondrial complex. Some studies identified methylated mRNAs originating from the mitochondrial genome ( 14 , 16 , 22 ), however, other studies were unable to support this finding ( 15 , 37 ).…”
Section: Introductionmentioning
confidence: 97%
“…Research groups focusing on non-coding RNAs have identified the m 5 C modification of mitochondrial tRNAs and one rRNA ( 11 , 28–30 ), indicating the presence of NSUN2 ( 29 , 31 ), NSUN3 ( 32 , 33 ) and NSUN4 ( 30 , 34–36 ) activity within the mitochondrial complex. Some studies identified methylated mRNAs originating from the mitochondrial genome ( 14 , 16 , 22 ), however, other studies were unable to support this finding ( 15 , 37 ).…”
Section: Introductionmentioning
confidence: 97%
“…Secondly, our research mainly focused on bioinformatic analysis, more experimental studies exploring the function of m 5 C on the different types of RNA and sites in COAD are in urgent need in future work. The m 5 C-Atlas database, a comprehensive database for decoding and annotating the m 5 C epitranscriptome, may be useful in the research ( Ma et al, 2022 ). Thirdly, overall survival between cluster Ⅰ and cluster Ⅱ had no significant difference, more m 5 C-related regulators and more cohort need to be included in future analysis.…”
Section: Discussionmentioning
confidence: 99%
“…m6A-Atlas ( Tang et al, 2021 ) and SRAMP( Zhou et al, 2016 ) were used to predict the m6A site of the lncRNAs; m5C-Atlas ( Ma et al, 2022 ) and RNAm5Cfinder ( Li et al, 2018 ) were used to predict the m5C site of the lncRNAs; m7GHub ( Song et al, 2020 ) and iRNA-m7G ( Chen et al, 2019 ) databases were used to predict the m7G site of the lncRNAs.…”
Section: Methodsmentioning
confidence: 99%